Microscopic characteristics and antioxidant activity of Uvaria boniana - Nguyen, Khanh Thuy Linh; Nguyen, Dinh Quynh Phu; Doan, Quoc Tuan; Nguyen, Thi To Quyen (Tạp chí Y Dược Huế, 2024)
Background and objectives: Uvaria, a genus within the Annonaceae family, encompasses around 150 species of flowering plants. Uvaria boniana is extensively found throughout Vietnam and is utilized in traditional medicine practices. The aim of this study was to determine the microscopic characteristics and evaluate the antioxidant activity of Uvaria boniana. Materials and methods: The stems and leaves of Uvaria boniana were collected in Huong Tra district, Thua Thien Hue province in October 2023. Micro-morphology of stems, leaves and powder properties were determined by the microscopic method. Antioxidant activity was assessed using the DPPH assay. Results: The microscopic characteristics of this species have been described. The methanol extract from the stem of U. boniana exhibited stronger antioxidant activity than the methanol extract from the leaf, with IC50 values of 45.19 ± 0.68 μg/mL and 70.94 ± 0.19 μg/mL, respectively. Conclusion: This is the first report on the microscopic characteristics and antioxidant activities of Uvaria boniana